Public policies and the image of the Brazil-Paraguay border: how does Youtube (de)valorize a cross-border territory? - Grechi, Dores Cristina; Lourenço, Rosenery Loureiro; Busón, Carlos Buesa (Anais Brasileiros de Estudos Turísticos, 2024)
Cross-Borders Territory are more than political-administrative lines; they are places of exchange, spaces of cooperation and competition, spaces of social, cultural, and economic interaction. They are complex and dynamic areas with multiple dimensions. The border analyzed in this article is between Brazil and Paraguay, in the twin cities of Ponta Porã and Pedro Juan Caballero, which have a free and continuous flow of people and goods. This research focuses on the perceived image of this border and its relationship with public policies that recognize its complexity and tourism potential. The study used YouTube videos to analyze the perception of these cities and discuss public policies and images of tourist destinations. Using the qualitative methodological approach of grounded theory, 68 videos and more than 14,000 comments were analyzed. Among the findings, the negative impacts of the presence of the PCC at the border and the actions of the Government stand out. The article argues that the lack of public policy initiatives and positive narratives in building the image of tourist destinations can lead to a distorted and detrimental image of these areas. Systematic strategies based on technical issues and cooperative actions among local actors are essential for leveraging the tourism potential of the territory.